Weakening of nurses practice delivering same day-access in primary care - Gláucia Bohusch; Sonia Acioli; Ricardo de Mattos Russo Rafael; Alex Simões de Mello; Juliana Roza; Halene Cristina de Armada e Silva (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To identify and analyze the weaknesses of the nurse's practice in meeting spontaneous demands in primary care units in the city of Rio de Janeiro. Method Qualitative study carried out in Rio de Janeiro, in 2016, with 20 nurses recruited unintentionally. The focus group and simple observation were applied, and data were subjected to thematic content analysis. Results The spontaneous demand service causes tensions and work overload. Nurses and community health agents are primarily responsible for organizing access. Final considerations There was a lack of understanding of the practice of spontaneous demand as part of care management, in addition to a polysemy related to the term. While for some, welcoming practices means greater autonomy, incorporating a larger scope of actions related to care and expanding their clinical practice; for others, they represent a stage that precedes medical consultation and a disorganizing element of care.